2007
DOI: 10.1001/archpsyc.64.8.886
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Depression in Age-Related Macular Degeneration

Abstract: Context: Age-related macular degeneration is a prevalent disease of aging that may cause irreversible vision loss, disability, and depression. The latter is rarely recognized or treated in ophthalmologic settings.Objective: To determine whether problem-solving treatment can prevent depressive disorders in patients with recent vision loss.Design: Randomized, controlled trial.Setting: Outpatient ophthalmology offices in Philadelphia, Pennsylvania.Patients: Two hundred six patients aged 65 years or older with rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
172
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(176 citation statements)
references
References 29 publications
2
172
0
2
Order By: Relevance
“…This difference is probably due to more emotionally engagement of female nurses as well as their hormonal differences (26,27). Rovner et al found in their study that there is a significant relationship between nurses' age and depression, which is similar with findings of the present study (28).…”
Section: Discussionsupporting
confidence: 89%
“…This difference is probably due to more emotionally engagement of female nurses as well as their hormonal differences (26,27). Rovner et al found in their study that there is a significant relationship between nurses' age and depression, which is similar with findings of the present study (28).…”
Section: Discussionsupporting
confidence: 89%
“…However, in the same population, cataract surgery did not appear to have a similar effect (Owsley et al, 2007b). Age-related macular degeneration has also previously been demonstrated to be associated with high rates of depression, anxiety and emotional distress (Berman and Brodaty, 2006) and in a randomized controlled clinical trial that compared the efficacy of problem-solving treatment with usual care in patients, treatment of depression was found to be effective in the short-term but the benefits were not maintained over time (Rovner et al, 2007). The impact of visual impairment on depression may depend on the severity and the origin of visual impairment and the duration of visual loss.…”
Section: Vision Loss As a Risk Factor For Depressive Symptomatologymentioning
confidence: 85%
“…Although some dimensions of emotional well-being may be maintained or improved through advanced old age, age-related vulnerabilities such as chronic health conditions may render the implementation of coping and self-regulation strategies difficult if not impossible, thus leading to the age-related increase in depressive symptoms (Charles, 2010). Some interventions, such as problem-solving treatment, may alleviate the effect of chronic health conditions for a short-term (Rovner et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…six months later (Rovner et al, 2007). Future studies are needed to evaluate the long-term effect of treatment to alleviate depressive symptoms in older adults.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation